THE EFFECT OF USING INSTAGRAM ON STUDENTS’ ENGLISH WRITING SKILL OF PROCEDURE TEXT AT EIGHTH GRADE OF SMP ISLAM AL-ULUM TERPADU - Ain Taszkiah Fadillah Lubis; Wariyati Wariyati (Jurnal Inovasi Penelitian, 2022)
The objective of the research was to determine whether there was a significant effect of the use of Instagram media on student achievement in students' writing mastery in procedural texts. This type of research is quantitative research and was conducted using two classes as research samples, namely class VIII-A as the experimental class consisting of 31 students and class VIII-C as the control class consisting of 31 students. In the data collection technique, the researcher conducted a pre-test, treatment and post-test by giving a test in the form of an example of a procedure text. The results of this study indicate that there is a significant effect of using Instagram on students' vocabulary mastery. This can be seen after the calculation and analysis of t-table df 60 (n= n-2= 31+31-2) at t-critical 0.05 obtained 1.67. If the comparison of the values ​​of to and tt, then the observed value is greater than the value of t-table or 9.59 > 1.67. This means that the eighth grade students of Al-Ulum Islamic Junior High School Terpadu apply Instagram media in learning procedure texts higher than those without Instagram media. After testing the research hypothesis, it turns out that the hypothesis is accepted.